Grain Market Integration in the Baltic Sea Region in the 19th Century - Fredrik N. G. Andersson; Jonas Ljungberg (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper explores the development of market integration within the Baltic Sea region as well as between the region and England, from the early 1840s to around 1890. It exploits two new datasets on grain prices. The paper applies a new method for measuring market integration by combining a dynamic factor model with wavelet analysis. A gradual yardstick is suggested and the role of distance analyzed. Wheat and rye markets became highly integrated whereas the cheaper grains lagged. Integration progressed geographically and conclusions emphasize traded volumes and transport cost.
Keywords: C21; N23; N53; 330; Baltic Sea Region; grain prices; market integration; wavelet analysis; dynamic factor model